On Г-n- (Anti ) Generalized Strong Commutativity Preserving Maps for Semiprime Γ-Rings - Abdulridha, Ahmed A.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2023)
In this study, we prove that let N be a fixed positive integer and R be a semiprime -ring with extended centroid . Suppose that additive maps  such that  is onto,  satisfy one of the following conditions  belong to Г-N- generalized strong commutativity preserving for short; (Γ-N-GSCP) on R   belong to Г-N-anti-generalized strong commutativity preserving for short; (Γ-N-AGSCP)  Then there exists an element  and  additive maps  such that  is of the form  and   when condition (i) is satisfied, and     when condition (ii) is satisfied